Autonomy‐Connectedness and Internalizing‐Externalizing Personality Psychopathology, Among Outpatients. Issue 7 (20th December 2012) - Bachrach, Nathan; Bekker, Marrie H. J.; Croon, Marcel A.
<x xml:space="preserve">Abstract</x> Objectives The aims of this research were to investigate gender differences in levels of autonomy‐connectedness, Axis I Psychopathology, and higher order factors of internalizing and externalizing personality psychopathology and, second, to investigate the association between these variables. Design The design of this research is cross‐sectional and multicentered. Methods We used self‐report questionnaires, factor analysis, and regression analysis. Results We found evidence for a significant role of autonomy‐connectedness in Axis I Psychopathology. This was especially true for women, who were found to be more sensitive to others and sensitivity to others was strongly associated with Axis I Psychopathology. Maybe due to the research sample no evidence was found for an association of autonomy‐connectedness with externalizing psychopathology. As to the role of autonomy‐connectedness in internalizing psychopathology, we found that a lack of self‐awareness or a capacity of managing new situations, combined with a high sensitivity to others, were associated with internalizing psychopathology. Women appeared to be more sensitive to others and to report higher levels of Axis I Psychopathology than men. Conclusion We conclude that autonomy‐connectedness plays an important role in Axis I Psychopathology as well as in internalizing Axis II pathology. Treatment of Axis I and internalizing Axis II psychopathology should therefore also focus on autonomy problems.